Intrusion and apical resorption of mandibular incisors in Begg treatment: anchorage bend or curve? - Lew Kenneth (Australasian Orthodontic Journal, 1990)
A statistical evaluation of the apical root resorption in mandibular incisors following Begg treatment in one group with anchorage bends and another group with anchorage curves showed no statistical difference. Although the overbite reduction in both groups were similar, the anchorage curve group was statistically more efficient in incisor intrusion when compared to the anchorage bend group (p<001).